THERAPY ADHERENCE OF 40-75 Y.O. HYPERTENSION RESPONDENTS USING MORISKY INSTRUMENT IN NGEMPLAK, SLEMAN, DIY (STUDY ON AGE, DEMOGRAPHY, SOCIAL, AND LIFE-STYLE FACTORS) - Millatina Jasmine; Nurjati Dwi Oktawati; Puspa Raras Damasari; Rita Suhadi (Sanata Dharma University, 2017)
Hypertension is systolic blood pressure (SBP) ?140mmHg and/or diastolic blood pessure (DBP) ?90mmHg. The risk factors of hypertension consist of age, life-style, demographic, and social factors. The risk factors have a significant association with antihypertension adherence. Adherence is the suitability of patient behavior to the prescribers recommendations. Morisky instrument can be used to measure the level of hypertension therapy adherence. The aims of this study were to assess respondents profile and therapy adherence based on age, life-style, demographic, social factors among the subjects in Ngemplak, Sleman, Daerah Istimewa Yogyakarta (DIY). Total respondents were 63 respondents. The observational study was done with cross-sectional design. Technique for determining the location used random sampling, data were collected by door to door in the villages of Morangan, Jimat, and Jelapan. Data analysis used chi square with 95% confidence level. There were 23.8% good adherent and 76.2% poor adherent subjects to antihypertensive medication. There was no significant difference between age, life-style, demographic, and social factors to the level of hypertension therapy adherence. However, it was found that controlled blood pressure (p-value0.01) were significantly associated with therapy adherence. This study also found that SBP at age 60-75 years and 40-59 years was significantly different (p-value 0.05).